The effect of forming parameter on multi-stage cold forging with 20MnTiB steel. Issue 5 (March 2016) - Xiao, Zhiling; Liu, Hua; Liu, Baixuan; Sun, Hongxing; Liu, Dan; Liu, Guanghui
Abstract The study aims to obtain the effect of forming parameters on multi-stage cold forging with 20MnTiB steel by performing a series of physical simulation and then verified by producing experiment of high-strength bolt. Physical simulation was performed through Gleeble 3500 compression tests; the mainly forming parameters such as strain rate (100 ∼101 ), deformation degree (20∼80 %), and number of stages were discussed. The results showed that the strain rate has little effect on the microstructure and the mechanical property. However, the number of stages and the deformation degree have an appreciable effect on the sample microstructure, of which the pearlite grain is fined and ferrite grain is elongated as fiber. The adiabatic thermal temperature rises from 20 to 142 °C with a 60 % deformation degree at a strain rate of 10 s−1 . Finally, the deformation properties of bolts can compare with the physical simulation results.